2017
DOI: 10.5604/12321966.1232085
|View full text |Cite
|
Sign up to set email alerts
|

Psychological consequences of IVF fertilization – Review of research

Abstract: There is a need to conduct studies on the effect of supportive social interactions for the functioning of couples undergoing IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 48 publications
(66 reference statements)
2
37
0
1
Order By: Relevance
“…As stress/psychological burden is the primary cause of dropout from the IVF program [8,9], this may be another reason to suggest that Endo-Gym® may help women start IVF and/or stay on the IVF program. As couples reported that due to the frustration of their inability to conceive naturally, even deciding on IVF is not easy [4], initial Endo-Gym® exercises may help bridge this difficult time of decision, which may than be further aggravated by later positive effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stress/psychological burden is the primary cause of dropout from the IVF program [8,9], this may be another reason to suggest that Endo-Gym® may help women start IVF and/or stay on the IVF program. As couples reported that due to the frustration of their inability to conceive naturally, even deciding on IVF is not easy [4], initial Endo-Gym® exercises may help bridge this difficult time of decision, which may than be further aggravated by later positive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding all the advances in technology, almost 80% of patients who undergo an IVF cycle will not eventually have a baby, and often cycles have to be repeated multiple times for conception and live birth (2.7 cycles on the average, with about 38% overall success after 3 cycles) [1]. Due to the frustration of being unable to conceive naturally, the very decision of undertaking infertility treatment is already difficult [4], and repeated unsuccessful cycles put the couples through enormous stress and maybe long-term negative effects [5]. Evidence points to that the anxiety and distress experienced may negatively affect the outcome of IVF itself [6,7] and result in the termination of the cycle before conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…IVF and PGD have associated emotional and psychological costs (Malina and Pooley, 2017). However, the use of PGD can help carrier parents to avoid the psychological impacts associated with passing on a known genetic disorder to their biological child (Beard et al, 2016;Ormondroyd et al, 2018).…”
Section: Ivf and Pgd For People With Vision Impairmentmentioning
confidence: 99%
“…Men and women dealing with infertility issues tend to feel guilty about not fulfilling their and their partners' needs, and can suffer from mood deterioration. Experiencing negative emotions connected with the inability to be a parent is a concern to women, especially to whom motherhood is an important aspect of their social role and their individual identity (Malina & Pooley, 2017).…”
Section: Feelings Of Inferioritymentioning
confidence: 99%